IMPLEMENTASI MADM PEMILIHAN ANGGOTA SQUAD E-SPORT MOBILE LEGEND MENGGUNAKAN MULTI-STAGE AHP - Erika Dewi Anggraini; Wiwien Hadikurniawati (Politeknik Caltex Riau, 2020)
E - Sports is an electronic-based sport that provided with internet or online networks, it takes more than one person to played. Mobile Legend is an online game that is often competed in E-Sport. Many competitions makes the player of Mobile Legend want to join. In a Mobile Legend, 5 players are required to join a group to play in the game. In this case, Nyanyah Squad only looked for 3 members to join the group. Many players want to join this group make the group leader confused, so a system is needed to help determine group members. In this study using the MADM (Multi-Atribute Decission Making) multi-stage AHP (Analytic Hierarchy Process) with the criteria of skills, winrates, statistics, roles and ranks, each of which has 3 sub criteria. The AHP (Analytic Hierarchy Process) method was chosen because it uses qualitative data collected from the results based on experience and intuition, in addition to quantitative data on complex problems can be solve according to the priorities needed. The final result of this study is ranking score alternative players and the players who can join the Nyanyah Squad. Keywords: efficiency, AHP, E - Sport members selection.